2015
DOI: 10.1257/mac.20120141
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rates, Leverage, and Business Cycles in Emerging Economies: The Role of Financial Frictions

Abstract: Countercyclical country interest rates have been shown to be an important characteristic of business cycles in emerging markets. In this paper we provide a microfounded rationale for this pattern by linking interest rate spreads to the dynamics of corporate leverage. For this purpose we embed a financial accelerator into a business cycle model of a small open economy and estimate it on a novel panel dataset for emerging economies that merges macroeconomic and financial data. The model accounts well for the emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 26 publications
9
70
0
Order By: Relevance
“…The first and closest to our work is the literature that has used dynamic, equilibrium models to account for business cycles in small open and emerging economies. A set of papers in this literature has explored the role of terms of trade variations in driving aggregate fluctuations in EMEs (Mendoza, 1995;Kose, 2002 Chang and Fernández, 2013;and Fernández and Gulan, 2014). We extend this strand of the literature by postulating a link between commodity prices and financial conditions in EMEs and quantifying its relevance when accounting for aggregate fluctuations in these economies within a structural framework.…”
Section: Introductionmentioning
confidence: 99%
“…The first and closest to our work is the literature that has used dynamic, equilibrium models to account for business cycles in small open and emerging economies. A set of papers in this literature has explored the role of terms of trade variations in driving aggregate fluctuations in EMEs (Mendoza, 1995;Kose, 2002 Chang and Fernández, 2013;and Fernández and Gulan, 2014). We extend this strand of the literature by postulating a link between commodity prices and financial conditions in EMEs and quantifying its relevance when accounting for aggregate fluctuations in these economies within a structural framework.…”
Section: Introductionmentioning
confidence: 99%
“…However, Chinese steel nature of the cost of borrowing from global financial markets for emerging markets, which can affect macroeconomic outcomes as sovereign risk is built into country interest rate spreads (Neumeyer and Perri, 2005;Uribe and Yue, 2006). As an economy improves, the interest rate on offer falls (Fernández and Gulan, 2015;Fernández et al, 2018). The literature has also shown that the omission of commodity prices for emerging markets leads to the overstatement of interest rate shocks on business cycles (Shousha, 2016).…”
Section: Robustnessmentioning
confidence: 99%
“…A recent paper by Gozzi et al (2015) documents key characteristics of corporate bonds markets in EMEs. 13 The academic literature that we use is: Neumeyer and Perri (2005), Uribe and Yue (2006), Aguiar and Gopinath (2007), Fernández and Gulan (2015), and Fernández et al, 2015a. The multilateral organizations and rating agencies that we look at are i) the IMF; ii) MSCI; and iii) JPMorgan.…”
Section: Sample Of Countries and Datamentioning
confidence: 99%
“…On the effects of global factors on EMEs' sovereign spreads, Arora and Cerisola (2001), González-Rozada and Levy-Yeyati (2008), and Ciarlone et al (2009) show that EMEs' sovereign spreads depend negatively on global financial conditions, such as U.S. interest rates, U.S. high-yield corporate spreads, and the volatility of U.S. stock prices, respectively. for the decisions of private agents (see, most recently, Fernández and Gulan, 2015). 6 Our work contributes to this literature by providing empirical evidence of the hypotheses derived from these models regarding the links between corporate bond spreads and economic activity.…”
Section: Introductionmentioning
confidence: 96%